READS - A Resource for Plant Non-coding Regulatory Sequence Analysis - Shahid, Saima; Elias, Sabrina M.; Biswas, Sudip; Seraj, Zeba I. (Plant Tissue Culture and Biotechnology, 2011)
Identification and analysis of regulatory sequences that control gene expression can be greatly facilitated by database-assisted bioinformatic approaches. READS (Regulatory Element Analysis DatabaSe) has been created as a web-accessible freely available database of plant non-coding regulatory sequences. It currently contains more than 300 known and putative promoters of constitutive as well as stress inducible genes belonging to diverse plants. The database has been manually curated with promoters collected mainly from scientific publications, thereafter cross-referenced with other resources (NCBI database, PubMed, PubMed Central). A user-friendly interface has been provided to allow easy access and analysis of data using different query options. A blast utility has also been provided, allowing users to search against all entries in the database. For each promoter, certain features such as expression data, GC content, core elements etc., were provided to assist in characterization of the regulatory sequences. To our knowledge, READS is the first plant promoter database that allows retrieval of sequences based on expression pattern. Thus the database can be utilized as a useful resource for identification of important putative regulatory cis-elements in promoters by analysis of upstream regions of hundreds of co-regulated or co-expressed genes. Such knowledge can also be of use for identifying minimal or stress inducible promoters for effective transgene expression. We aim to provide the most up-to-date collection of promoters of well-characterized stress inducible and constitutively expressed genes from many plant species. Hence, this resource will be updated regularly to incorporate new sequences. READs is available at http://www.pbtlabdu.net/READS/. Key words: Promoter database, stress inducible, constitutive, gene expression, cis-element D.O.I. 10.3329/ptcb.v20i2.6916 Plant Tissue Cult. & Biotech. 20(2): 211-223, 2010 (December)